CONJUGATED LINOLEIC ACID: IMPLICATION ABOUT THE CARDIOVASCULAR FUNCTION ABSTRACT (Fiep Bulletin - online, 2012)
The conjugated linoleic acid (CLA) refers to a set of isomers of the octadecadienoic produced naturally by bacteria present in the rumen of the animals, which has been used as alimentary supplement, as it potential body fat reduction effect. Several biological activities are attributed to the compound, such as cardiovascular protector, although the mechanisms which CLA interferes in this function are still not established. Primarily, the CLA acts on the serum lipid profile being able to alter the levels of total cholesterol, LDL, VLDL, HDL and TG, important risk factors for the CVD, such action is probably due to the capacity of regulating the synthesis of lipids, being associated also to reducing acting of fat and consequently, the body weight. The CLA also appears to have effect on the atherogenic process, observing positive effects over the atherosclerotic places established and in the process of deposition of lipids in the vessels, besides establishing for formatted places. Finally, towards the arterial pressure, the CLA seems to have the capacity of reducing blood pressure. However, the results found are not consistent yet, specially, in models with humans, thus, future studies must be done to determine a daily recommended dose and the safety of its use.
Keywords: CLA; CARDIOVARCULAR; LIPIDS